Post-secularism, Multiculturalism, Human Rights, and Religion in Ontario - Seljak, David ca. 20./21. Jh. (Studies in religion, 2016)
Most Canadians believe that they have resolved the issue of religious freedom—as well as the problems of the injustice of Christian privilege and discrimination based on religion—by redefining the social order according to Canadian models of secularism, multiculturalism, and human rights. Typical of this resolution were the protections against discrimination based on religion or “creed” in the Ontario Human Rights Code, drafted in 1962. However, dramatic social and demographic changes in Ontario over the last fifty years have presented the efforts of the Ontario Human Rights Commission to protect and promote religious freedom with unexpected challenges. New forms of ethno-racial and religious pluralism, more widespread secularism, more religious hybridity and innovation, and greater degrees of individualized expression of religious identity have forced the Commission to rethink its policies pertaining to religious freedom. The Commission is wrestling with the fact that not only has Ontario become more religiously diverse in terms of the number of world religions and sub-divisions in those traditions, but religion in Ontario is expressing itself in unprecedented forms. At the same time, jurisprudence and public attitudes about the role of religion in secular, liberal democracies are also evolving. This article examines the Commission’s treatment of religious freedom in its policy work on balancing competing human rights and protection of freedom based on creed. It analyzes the Commission’s challenges in formulating policies around religious freedom by examining the interaction between secularism, multiculturalism, and human rights culture in the context of the transition of Canada’s social order to a post-secular society.